Ukraine Russia's War and the Future of the Global Order - Cox, Michael (LSE Press, 2023)
The full-scale invasion of Ukraine by Russia in 2022 has not only caused immense suffering inside the country, and among its people, it has shifted the political landscape in Russia for the worse, altered the strategic map of Europe, and created division and economic pain in the rest of the world. In this volume, a group of internationally acclaimed academics - many originally from Ukraine or Russia - examine the deep causes of Putin's war, the role played by other actors such as China and the United States, the severe consequences for the many millions of Ukrainians displaced from their home and country, the impact on the West and the Global South and the challenges confronting Ukraine when the war finally comes to an end. Part of the LSE Public Policy Review Series, Ukraine: Russia's War and the Future of the Global Order offers a rigorous intellectual response to this extreme humanitarian crisis and considers the implications for the future of Ukraine and the transformed global order.